Manual de plantas medicinales. Enfermedades, plagas, cultivo, indicaciones y generalidades. - Ruiz. Guardado, Marta (2015)
The scope of herbal medicine plants ranging from with slight action as chamomile and mint until power¬ful as digital (Digitalis purpurea), where digitalis is obtained. Between these two extremes, the spectrum of medicinal herbs with an important medical significance was founded. The World Health Organization (WHO) notes that of 119 drugs derived from plants, about 74% are used in modern medicine. In order to obtain an optimum quality of medicine is vital, the perfect individualization of plant, the knowledge of the specific part (s) the plant to use. Therefore, the manual about medicinal plants with the informa¬tion to agronomic and medicinal evaluation of some species was created. It is remarkable the fact, of grouping first time, plants for medicinal purposes and relate them with pathogens and pests that can in¬fluence in the quality of the drug, because they could decrease the performance of active principal, due to damages on the plant, such as: necrotic on leaves, decay, loss of the leaf blade and effects on chloro¬phyll. The manual provide, an integrated management of pest in crops of the species with an optimiza¬tion of functional biodiversity with minimum negative effects on the environment is a useful tool for stu¬dents, professionals, specialists and interested communities in the use and cultivation of green medicine. Keywords: Herbal, botanical description, cultivation, pests.